Antibacterial Effect of Silver Nanoparticles on Polymicrobial Biofilms in Endodontics: Systematic Review and Meta Analysis - Iván Olivares-Acosta; Lilian Beatriz Romero-Sánchez; Nuria Patiño Marín; Marco Felipe Salas Orozco (Journal of Nanotechnology)
This systematic review investigates the antibacterial effects of silver nanoparticles (AgNPs) on polymicrobial biofilms in endodontics, emphasizing their potential enhancement of traditional treatment methods. Recognizing the limitations of current endodontic disinfectants in fully eradicating complex biofilms, this study focuses on the synergistic potential of AgNPs to improve antimicrobial efficacy. Utilizing a systematic approach based on PRISMA guidelines, the review draws on studies from databases like PubMed, Web of Science, and SCOPUS up to 2024. The included research specifically examines the role of AgNPs in various endodontic applications against resilient biofilms, adhering to strict inclusion criteria that demand clear methodology and measurable outcomes. The results suggest that AgNPs can significantly augment the biofilm disruption capabilities of conventional antimicrobials, potentially due to their ability to modify the biofilm matrix and enhance agent penetration. However, the effectiveness varies depending on the nanoparticle concentration and application technique, indicating a need for further optimized studies. In conclusion, while AgNPs show promise in enhancing endodontic antimicrobial protocols, additional in vivo research is necessary to establish standardized, effective, and safe clinical applications. The review highlights the complex interactions between nanoparticle properties and biofilm biology, underscoring the importance of further investigation in this area.